The Role of Hotel Tax on Bandung City Regional Income - Tiara Riskawati Trisnadi; Valentina Cahyaningtyas; Devi Kusnanda Putri; Paskalino Siubera Udam; Joni Alwi; Nana Istiqomah; Galih Wicaksono (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
Abstract. Reduced dependence on funds from the central government, proving that the receipt of Regional Original Revenue (PAD) is very good for implementing regional goverment. This is the same as the effectiveness and contribution of local taxes to local revenue, one of which is hotel tax. Hotel tax is a tax on services provided by hotels with payment. Hotel tax is included in the type of local tax that has the large contribution to the receipt of Regional Original Revenue (PAD) of Bandung City. This research aims to calculate the effectiveness and contribution of hotel tax to Bandung City's Regional Original Revenue (PAD). The method used for this research is descriptive quantitative, in the form of explanation and analysis related to numbers which include the target and realization of hotel tax revenue and Regional Original Revenue (PAD) of Bandung City in the period 2019-2022. The results of the study indicate that the effectiveness of hotel tax revenue in Bandung City has fluctuated in the 2019-2022 period, the contribution of hotel tax to PAD is also still considered less than optimal.